Food-borne pathogens : methods and protocols - Adley, Catherine C., ....- (Totowa : Humana, 2006)
This volume presents emerging molecular methods of analyzing for food pathogens. It contains methodologies for the laboratory isolation and identification of the three groups of organisms that cause food-borne disease: bacteria, viruses, and parasites. These methods clearly demonstrate the direction in rapid identification systems presently being developed. The methodologies presented in "Food-Borne Pathogens" will be utilized by research scientists and food technologists, on an ongoing basis throughout their work.
Keywords: Voedingsmiddelenonderzoek